2012
DOI: 10.1016/j.physleta.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Hirota method for oblique solitons in two-dimensional supersonic nonlinear Schrödinger flow

Abstract: In a previous work[1] exact stable oblique soliton solutions were revealed in two dimensional nonlinear Schrödinger flow. In this work we show that single soliton solution can be expressed within the Hirota bilinear formalism. An attempt to build two-soliton solutions shows that the system is "close" to integrability provided that the angle between the solitons is small and/or we are in the hypersonic limit. PACS numbers: 47.40.Nm, 03.75.Kk, 05.45.Yv IntroductionThe nonlinear Schrödinger (NLS) flow is ubiq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For greater radius more pairs of oblique solitons are generated. Interaction of solitons was studied in [15,16] where it was found that the angle between dark solitons decreases as the obstacle radius increases for a fixed supersonic velocity of the flow. In previous experimental works [13,17,18] the existence of such nonlinear structures were suggested.…”
Section: Introductionmentioning
confidence: 99%
“…For greater radius more pairs of oblique solitons are generated. Interaction of solitons was studied in [15,16] where it was found that the angle between dark solitons decreases as the obstacle radius increases for a fixed supersonic velocity of the flow. In previous experimental works [13,17,18] the existence of such nonlinear structures were suggested.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be seen from figure 2(b) that the amplitude of the kink wave increases with the increase of parameter α 1 . 4), and equation (3) is two-kink-breather solution of the YTSF equation as follows: From equation (10), it is easy to know that the existence conditions of the nonsingular solution of equation (9…”
Section: Two-kink-breather Solutionmentioning
confidence: 99%
“…Many studies of nonlinear wave interactions have been widely used in the fields of optics, plasma physics, fluid dynamics and solid state physics, etc [1][2][3][4][5]. With the development of the soliton theory, it appears some nonlinear waves such as solitons, rouge waves, kink solitons, lumps, breathers, kink-breathers, etc [6][7][8][9][10][11]. Among which, kink solitons and breathers are two typical categories of solitons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation